2004
DOI: 10.1021/jo048842u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Some 6-Substituted-2,4-dimethyl-3-pyridinols, a Novel Class of Chain-Breaking Antioxidants

Abstract: The synthesis and study of a series of 6-substituted-2,4-dimethyl-3-pyridinols having interesting antioxidant properties is reported. The general synthetic strategy leading to the compounds involved a low-temperature aryl bromide-to-alcohol conversion as the last step. 2,4-dimethyl-3-pyridinol (1a), 2,4,6-trimethyl-3-pyridinol (1b), and 2,4-dimethyl-6-(dimethylamino)-3-pyridinol (1d) were thus prepared from the corresponding 3-bromopyridine precursor. The methoxy derivative 2,4-dimethyl-6-(methoxy)-3-pyridinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 49 publications
2
66
0
1
Order By: Relevance
“…The effectiveness of an antioxidant can depend on a variety of factors, including the fatty acid profile of the oil or fat, the amount of naturally occurring antioxidants and storge or conditions (Knothe, 2007). Natural antioxidants such as tocopherols and tocotrienols in vegetable oils is affected by the refining process (Wijtmans et al, 2004). Antioxidants such as phenols and amines either have a hydrogen atom, phenols becom quinones or react with a radical in an addition fashion.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of an antioxidant can depend on a variety of factors, including the fatty acid profile of the oil or fat, the amount of naturally occurring antioxidants and storge or conditions (Knothe, 2007). Natural antioxidants such as tocopherols and tocotrienols in vegetable oils is affected by the refining process (Wijtmans et al, 2004). Antioxidants such as phenols and amines either have a hydrogen atom, phenols becom quinones or react with a radical in an addition fashion.…”
Section: Methodsmentioning
confidence: 99%
“…An unidentifi ed peak at retention time 5.45 min in our previously published chromatogram of a 7-DHC free radical oxidation mixture was confi rmed to be epox- tests and in studies of neuronal oxidative stress (63)(64)(65)(66), and experiments were therefore carried out with SLOS HFs to assess the potential of these antioxidants to reduce the levels of oxysterols. SLOS fi broblasts in lipid-defi cient serum were incubated for 5 days in the absence or presence of 10 M antioxidant 3 ( Fig.…”
Section: Dhceo Can Be Formed From 5 ␣ 6 ␣ -Epoxycholest-7-en-3 ␤ -Olmentioning
confidence: 99%
“…Hence, it can be suggested that suitable additives can be added to the fuel to increase its shelf life and storage characteristics. Some additives for biodiesel storage found in literature are pyrimidinols [29], butylated hydroxytoluene, butylated hydroxyanisol, tert-butyl hydroquinone, propyl gallate, ethylenediaminetetraacetic acid, citric acid, phosphoric acid, and amino acids [30].…”
Section: Storage Propertiesmentioning
confidence: 99%